New migrations in Portugal: Labour markets, smuggling and gender segmentation - Peixoto, João (2022)
In the last three decades, Portugal has undergone deep changes regarding international migration. Firstly, it has become an important receiver of foreign international migrants from Africa, namely the ones coming from the ex-colonies, now independent countries. Secondly, it witnessed a growing presence of Brazilians, which turned from a narrow middle-high class group of immigrants, to a very large number of middle-low and low class immigrants. Thirdly, it observed a progressive diversification of national origins, mainly represented by the recent and vast Eastern European community, but also visible in dozens of other growing foreign nationalities. In this paper, the focus will be on the role played by labour markets in the growth of new migrations, particularly in what is linked to the importance of smuggling and gender segmentation. Regarding smuggling, the strong recent expansion of the Portuguese economy, accompanied by frequent informal relationships in the labour market, largely explain the surge in the number of immigrants. These migrants often entered the country in an irregular way, using the services of smugglers and traffickers, and performing the bottom jobs of the professional ladder. Given the demand for a flexible labour force and the government’s restrictive immigration policy, the objective needs of the labour market were often met by irregular channels of migration. Gender was also a part of the process, since the segmentation of the labour market was increasingly based on ethnic and gender lines. The growth of female related jobs, from domestic and industrial cleaning to caring, and including the sex industry, explained why gendered avenues were built for labour immigration. Although most of the recent labour cycles were dominated by male workers, an increasing fraction was composed of women. Except for the case of trafficking, where exploitation is persistent, women may have acquired in this immigration process an increased but problematic autonomy.